Effectiveness of acupuncture on glycolipid metabolism in patients with coronary heart disease: A systematic review and meta-analysis - Yuxin Sun; Yu Liu; Jian Xiong; Xiao Li; Ying Wei; Qianhua Zheng; Xiang Li; Wenchuan Qi; Fanrong Liang (Complementary Therapies in Medicine)
Objective: Disorders of glycolipid metabolism are important pathogenic factors leading to coronary artery disease, and there is no safe and effective comprehensive treatment, while acupuncture has a certain efficacy in heart disease and disorders of glycolipid metabolism. To assess the effects of acupuncture on glycolipid metabolism in patients with coronary heart disease, we conducted a systematic review and meta-analysis. Methods: From the time of library construction to August 18, 2023, Searches were conducted in eight databases, with no language restriction. Only RCTs that included acupuncture as a sole or secondary effect on glucose-lipid metabolism in coronary heart disease were included.Our primary outcome indicators were Low-density lipoprotein cholesterol(LDL-C), Hemoglobin A1c(HbA1c). Our analyses were conducted in strict accordance with the PRISMA statement, and the researchers used the Cochrane Handbook for literature screening and data extraction, the “Risk of Bias” tool (ROB.2) for assessing risk of bias, and RevMan (version 5.3) for meta-analysis of outcome metrics, and the GRADE criteria for assessing quality of evidence. Assessing the quality of acupuncture literature using the Standards for reporting interventions in clinical trials of acupuncture. Results: Our analysis included 18 eligible RCTs (N = 1346 participants). For the primary outcome metrics, acupuncture combined with standard treatment was effective in reducing LDL-C (SMD =-0.56; 95 % CI, −0.75 to −0.38; P < 0.00001), and HbA1c (MD = −1.15; 95 % CI, −1.73 to −0.58; P < 0.0001). For secondary outcome measures, combination therapy improved TC (SMD = −0.97; 95 % CI, −1.44 to −0.51; P < 0.0001), TG (MD = −0.39; 95 % CI, −0.58 to −0.20; P < 0.0001), hs-CRP (MD = −0.98; 95 % CI, −1.43 to −0.52; P <0.0001), 2hPG (MD = −1.45; 95 % CI, −1.74 to −1.16; P < 0.00001), and ORR (RR, 1.27; 95 % CI, 1.19–1.36; P < 0.00001) levels more than standard therapy alone.However, the combination therapy did not prevail in lowering HDL-C (MD = 0.11; 95 % CI, 0.07–0.14; P < 0.00001) compared with standard therapy alone. Meanwhile heterogeneity analysis showed that After coronary heart disease intervention, acupuncture was able to reduce TC (SMD = −0.85; 95 % CI, −1.37 to −0.33; P = 0.001), TG (MD = −0.14; 95 % CI, −0.24 to −0.04; P = 0.004) levels, but did not dominate in lowering LDL-C. Conclusions: Acupuncture effectively regulates glycolipid metabolism in coronary artery disease, serving as an adjuvant treatment. It may aid post-PCI healing via lipid metabolism regulation, but rigorous, large-scale, long-term RCTs are needed for validation.